Franklin Roosevelt’s Foreign Policy and the Welles Mission - Rofe, J. author. aut Link
IX, 270 p. 1 illus.
Keywords: A new and original analysis of the mission undertaken by FDR's Secretary of State during the Phoney War, Rofe's work explains the motivations and goals of Roosevelt through an analysis of the president's foreign policy and of the nature of the Anglo-American relationship of the time.